Glaucoma: a new approach for detection in rural eye care - Mawale, Mahesh B.; Kuthe, Abhaykumar; Dhakate, Ravishekhar; Pawane, Padma; Dahake, Sandeep W. (International Journal Of Community Medicine And Public Health, 2017)
Background:There is a dare need of a device for the measurement of intraocular pressure by making the contact of plunger with closed eyelid eliminating the need of anesthesia and expert ophthalmologist. The main purpose of this study is to develop a device for the indicative measurement of intraocular pressure (IOP) of eyeball, a key cause for glaucoma. Methods:TRIZ ‘The theory of solving inventor’s problem’ is an era of technical development and innovation. Developing a device for detecting glaucoma by using TRIZ and top ten innovative principles recommended by expanded TRIZ matrix can exceed the disadvantages that classic tonometer has. The field of Ophthalmology will be experiencing a paradigm shift towards the use of collaborative approach of classical and expanded TRIZ. Results:In early diagnosis and treatment of glaucoma accurate measurement of IOP is important. The methods and devices which are available for the measurement of IOP have their own limitations which cause discomfort to the patients during measurement and needs anesthesia. This approach shows a good result in development of a device for detecting glaucoma in patient’s eye through eyelid instead of cornea. Conclusions:There is a substantial need for early detection and diagnosis of glaucoma in rural and remote areas (worldwide). This study has demonstrated the development of new device for detection of glaucoma using TRIZ, will help the medical practitioners in rural and remote areas for detection of glaucoma.